Renal hyperfiltration as risk factor of major adverse cardiovascular events in patients with acute myocardial infarction - Jin Sug Kim; Weon Kim; Hyo-jin Lee; Kyung Hwan Jeong; Su Jin Jeong; Myung Ho Jeong; Jin-Yong Hwang; Seung Ho Hur; Hyeon Seok Hwang (Scientific Reports)
Abstract The potential interaction between the heart and kidneys is thought to contribute to the development of renal hyperfiltration (RHF). However, the clinical implications of RHF remain unclear in patients with acute myocardial infarction (AMI). A total of 9561 AMI patients with estimated glomerular filtration rate (eGFR) ≥ 60 mL/min/1.73 m2 were enrolled from a large nationwide cohort. RHF was defined as eGFR > 90th percentile after multiple adjustments. The primary endpoint was a combination of 3 year major adverse cardiovascular events (MACEs) after AMI treatment. The cumulative event rate of MACEs was significantly higher in patients with RHF. In multivariable Cox-regression analysis, RHF increased the 1.34-fold risk of MACE (95% confidence interval [CI] 1.12–1.62) compared to those without RHF. Patients with RHF had a significantly higher risk of all-cause mortality (hazard ratio [HR] 1.64; 95% CI 1.25–2.14) and cardiac death (HR 1.78; 95% CI 1.26–2.51). There was a U-shaped association between the adjusted risk of MACEs and eGFR, with the risk increasing as eGFR exceeded approximately 100 mL/min/1.73 m2. The results demonstrated a consistent pattern in the 1:1 PS-matched population. Our study offers new insights into the risk stratification of AMI patients with RHF.